Adipose-Derived Stem Cells Cocultured with Chondrocytes Promote the Proliferation of Chondrocytes - Jie Shi; Jiulong Liang; Bingyu Guo; Yu Zhang; Qiang Hui; Peng Chang; Kai Tao (Stem Cells International)
Articular cartilage injury and defect caused by trauma and chronic osteoarthritis vascularity are very common, while the repair of injured cartilage remains a great challenge due to its limited healing capacity. Stem cell-based tissue engineering provides a promising treatment option for injured articular cartilage because of the cells potential for multiple differentiations. However, its application has been largely limited by stem cell type, number, source, proliferation, and differentiation. We hypothesized that (1) adipose-derived stem cells are ideal seed cells for articular cartilage repair because of their accessibility and abundance and (2) the microenvironment of articular cartilage could induce adipose-derived stem cells (ADSCs) to differentiate into chondrocytes. In order to test our hypotheses, we isolated stem cells from rabbit adipose tissues and cocultured these ADSCs with rabbit articular cartilage chondrocytes. We found that when ADSCs were cocultured with chondrocytes, the proliferation of articular cartilage chondrocytes was promoted, the apoptosis of chondrocytes was inhibited, and the osteogenic and chondrogenic differentiation of ADSCs was enhanced. The study on the mechanism of this coculture system indicated that the role of this coculture system is similar to the function of TGF-β1 in the promotion of chondrocytes.